Evolution and changes in the blood coagulation system. A reflection - Osorio, José Henry; Quenán, Yoccner Edilson; Borja Gómez, Wilmer (Universidad y Salud, 2013)
The objective of the present review is to analyze updated concepts related to blood coagulation, and to generate a reflection about it. Information from the last 50 years including the BBCS-LILACS, “Fuente Académica”, IBPsycINFO, IB-SSCI, IB-SciELO, Scopus and Scirus databases, as well as historical articles, texts and references cited in public published papers to date were analyzed. Pertinent information related to the objectives proposed in the present article was found and analyzed. It was then divided into two sections as follows: history of coagulation and the cellular model of hemostasis. It can be concluded that new postulates have been presented today for a better understanding of the function of coagulation cascade, which allow knowing and differentiating in an improved way such process. Nowadays the classic model of blood coagulation shows several observations and then it is unlikely that in physiological conditions this can useful.